Pengaruh Pendapatan Perkapita Terhadap Tabungan Di Provinsi Riau - Elvina Safitri; Alfiatun Oktafia Pertiwi (Journal of Innovative and Creativity, 2026)
The higher a country's economic growth, the more it can improve the welfare of its people, which in turn impacts the pace of development. Economic development and economic growth are closely related. Economic development requires capital. Capital can be obtained from both domestic and international sources. One source of capital is savings, making the collection of public funds by banks essential. However, it's important to note that savings are significantly influenced by economic conditions. This is not just a micro-level factor but also a macro-level one. One fundamental issue affecting individual savings is their ability to save. Mankiw's book, Macroeconomics, explains that individuals in the working age group save more than those past this age (retired individuals). It's clear that the working age population has the potential to earn more than older people. Therefore, this is certainly related to income. However, it's also possible that older people have higher incomes than working-age individuals. In research, this income is referred to as per capita income. Based on this, this study aims to examine the extent to which per capita income can influence savings, focusing on Riau Province. The research is descriptive and uses secondary data. The results conclude that per capita income significantly influences savings in Riau Province.